Human Capital Development and Economic Growth in Suriname - Gavin Ooft; Karel Eckhorst (Centrale Bank van Suriname, 2013)
This paper investigates the effects of human capital on economic growth in Suriname for the period 1971 to 2011. Many empirical studies indicate that the accumulation of this form of capital has a significant impact on macroeconomic growth. At the same time some studies show an overestimation of the role of human capital in growth. In this research, we measure human capital through education indicators. We argue that the development of human capital stimulates countries to be innovative and develop modern production technology to catch up with more developed countries. The findings of this investigation indicate that human capital also affects long-run macroeconomic growth in Suriname through primary and secondary education.
Keywords: O11; O15; C22; 330; Human Capital; Economic Growth; Regression Analysis